2019
DOI: 10.3390/w11030467
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Bacteria in Lakes with Different Chlorophyll Content and Investigation of Their Respiratory Activity through a Long-Term Microcosm Experiment

Abstract: Bacterial community structure and metabolism are critical factors for ecosystem functioning since they affect remineralization of nutrients and carbon flow. We used Illumina sequencing of 16SrRNA V3-V4 regions to investigate whether bacterial assemblage composition differs between four samples from two lakes in the geographic region of Epirus (Greece) characterized by distinct oligotrophic to eutrophic/hypereutrophic conditions as revealed by chlorophyll-a values. We found high similarity (>60%) for bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 72 publications
(87 reference statements)
0
4
0
Order By: Relevance
“…Though the collection vessels were filled to the lip, closed with an air-tight cap, and kept on wet-ice for less than 2 h, some organisms, such as obligate anaerobes, may have been lost. Many other metagenomic investigations of environmental water samples have stored samples on wet-ice before microbe isolation ( Yannarell et al, 2003 ; Shade et al, 2007 ; Van Rossum et al, 2015 ; Uyaguari-Diaz et al, 2016 ; Linz et al, 2017 ; Karayanni et al, 2019 ; Mohiuddin et al, 2019 ). Thus, the collection procedure that were used by the students is within the norms of basic research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the collection vessels were filled to the lip, closed with an air-tight cap, and kept on wet-ice for less than 2 h, some organisms, such as obligate anaerobes, may have been lost. Many other metagenomic investigations of environmental water samples have stored samples on wet-ice before microbe isolation ( Yannarell et al, 2003 ; Shade et al, 2007 ; Van Rossum et al, 2015 ; Uyaguari-Diaz et al, 2016 ; Linz et al, 2017 ; Karayanni et al, 2019 ; Mohiuddin et al, 2019 ). Thus, the collection procedure that were used by the students is within the norms of basic research.…”
Section: Discussionmentioning
confidence: 99%
“…A similar pattern was observed in a separate study of the Great Lakes, canals, and streams of the Niagara Peninsula ( Mohiuddin et al, 2019 ). In contrast, a study of oligotrophic versus eutrophic lakes in Greece showed greater species diversity in the eutrophic samples ( Karayanni et al, 2019 ). These results suggest that trophic status can alter the freshwater prokaryote diversity, but a general rule on the relationship between nutrient level and prokaryote community diversity has not been established.…”
Section: Introductionmentioning
confidence: 94%
“…6C ). Hgcl clade taxa have previously been associated with eutrophic aquatic settings, which could correspond to diatom overabundances that could indicate algal bloom states ( 83 ). These ASVs also displayed heightened relative abundances in sample sites binned into low HMP and HET, yet no change in relative abundance in B 1 bins, indicating evidence for precursor auxotrophy, drawdown, and limited thiamine biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Sporichthyaceae ASVs captured the above trend and the hgcl clade (genus annotation of Sporichthyaceae) was the most abundant genus across all samples sites yet were exceedingly low in relative abundances in Battle and Butte Creeks (Figure 6C). Hgcl clade taxa have previously been associated with eutrophic aquatic settings, which could correspond to diatom overabundances that could indicate algal bloom states (83). These ASVs also displayed heightened relative abundances in sample sites binned into low HMP and HET, yet no change in relative abundance in B1 bins, indicating evidence for precursor auxotrophy and drawdown.…”
Section: Relationship Between Microbial Taxa and Dtrcsmentioning
confidence: 91%